Analisis Pola Rekrutmen Prajurit TNI AL Tahun 2020 Pada Satuan Pendidikan Sorong Dalam Rangka Penyediaan Prajurit Koarmada III - Lakipundu Rassa, Andri Yusuf Kristmas; Lestari, Amin (Universitas Trunojoyo Madura, 2021)
The study aims to improve the quality and quantity of Indonesian Navy human resources in Eastern Indonesia, especially in the working area of the Fleet Command III, so the recruitment of Indonesian Navy soldiers will fill the needs of personnel in Eastern Indonesia. The object of research in the form of individuals are the officers or personnel officers who handle the recruitment of candidates of the Indonesian Navy soldiers. As for the object of research in the form of organizations, namely Spersal, Lapetal Disminpersal, Panda Lantamal X Jayapura, Panda Lantamal XI Merauke and Panda Lantamal XIV Sorong. This study uses the following analytical techniques: grouping data based on the characteristics of informants, conducting a qualitative approach to find out in detail how descriptive study of recruitment patterns in each Panda, then combining literature review, data from the reality in the field, and the experience of informants to gain a general knowledge of the recruitment pattern in the Sorong Education Units. The results showed that the recruitment pattern at the Sorong Educational Service which supervised Panda Lantamal X Jayapura, Panda Lantamal XI Merauke and Panda Lantamal XIV Sorong, had been going well, regardless of the obstacles they faced.